School and Parent Collaboration Model to Support Student Learning Outcomes - Widhiarto, Nurul; Haryanto, Sigit (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe and design an effective school and parent collaboration model in supporting student learning outcomes. The research approach used is qualitative descriptive explorative with the subjects of the principal, teachers, and parents of MI Muhammadiyah Godog Polokarto Sukoharjo. Data were obtained through in-depth interviews, participatory observations, and documentation studies, then analyzed using the Miles and Huberman technique which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that effective forms of collaboration include open two-way communication, active participation of parents in school activities, mentoring children's learning at home, and parent capacity building programs. However, there are obstacles such as time constraints, gaps in understanding learning methods, and the absence of systematic collaboration guidelines. This study resulted in a comprehensive and adaptive collaboration model design which is expected to be a practical guideline for schools to realize sustainable synergy, so that it has a positive impact on improving student learning outcomes in both academic and character aspects.